Analisis Risiko Investasi dengan Simulasi Monte Carlo Pada Saham Kelapa Sawit di Indonesia - Leny Yuliyani; Reny Wulandari; Muh. Idham Kurniawan (Jurnal MeA (Media Agribisnis), 2026)
Stock investment offers profit opportunities but also involves risk due to price fluctuations that create uncertainty in returns. This risk is relevant for palm oil sector stocks on the Indonesia Stock Exchange, which are sensitive to global CPO price dynamics, trade policies, exchange rates, and global economic conditions, leading to relatively high volatility. This study aims to measure the potential maximum loss that may occur using Value at Risk (VaR) based on Monte Carlo simulation. VaR measurement is conducted on five issuers (SMAR, LSIP, AALI, ANJT, and SGRO) with 1,000 iterations and confidence levels of 95%, 97.5%, and 99%. The results show that at all confidence levels, LSIP stock consistently has the highest risk, with the largest VaR values of −52.01% at the 95% confidence level, −61.98% at the 97.5% confidence level, and −73.56% at the 99% confidence level, while AALI stock shows the lowest risk with relatively small VaR values of −2.6% at the 95% confidence level, −3.11% at the 97.5% confidence level, and −3.7% at the 99% confidence level. These findings indicate that Monte Carlo VaR can provide an overview of the investment loss boundary and support more rational and measurable investment decision-making in palm oil stocks.